2006
DOI: 10.1111/j.1365-3040.2006.01614.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical signals and their physiological significance in plants

Abstract: Electrical excitability and signalling, frequently associated with rapid responses to environmental stimuli, are well known in some algae and higher plants. The presence of electrical signals, such as action potentials (AP), in both animal and plant cells suggested that plant cells, too, make use of ion channels to transmit information over long distances. In the light of rapid progress in plant biology during the past decade, the assumption that electrical signals do not only trigger rapid leaf movements in '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
507
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 559 publications
(530 citation statements)
references
References 79 publications
15
507
0
8
Order By: Relevance
“…15 EPWs are generated by mechanical and physical stimuli [16][17][18] and depend on voltage-activated and possibly mechanosensitive channels along sieve tubes. 14,19 Our recent study 13 showed, that forisomes at 3-4 cm from the stimulus site dispersed 15-45 sec after burning the leaf tip.…”
Section: Modes Of Sieve-plate Occlusionmentioning
confidence: 99%
“…15 EPWs are generated by mechanical and physical stimuli [16][17][18] and depend on voltage-activated and possibly mechanosensitive channels along sieve tubes. 14,19 Our recent study 13 showed, that forisomes at 3-4 cm from the stimulus site dispersed 15-45 sec after burning the leaf tip.…”
Section: Modes Of Sieve-plate Occlusionmentioning
confidence: 99%
“…Electrical signals play an important role in triggering photosynthetic response across long distances within the plant, and may regulate a variety of physiological responses in plants, including elongation, growth, respiration and water uptake [5]. Many investigators, however, doubt the signaling value of electrical activity in plants, and the subject remains an area of active research.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of electrical potentials in plants indicates that electrical signaling is a major system to transmit information over long distances throughout its organs. The reason why plants have developed pathways for electrical signal transmission is probably related to its need to respond rapidly to environmental stress factors (Fromm & Lautner, 2007). Electrophysiological studies of longdistance signals in plants and animals contribute to our knowledge of the living world by revealing important similarities and crucial differences between plants and animals, in an area that might be directly related to their different capacities to respond to environmental change.…”
Section: Introductionmentioning
confidence: 99%
“…Plant neurobiology is aimed at establishing the structure of information networks that exist within the plant, which is expressed as responses to environmental stimuli by means of electrochemical signals (Baluška et al, 2004;Trewavas, 2005). These signals seem to complement other plant signals: hydraulic, mechanical, volatile and hormonal, already well documented in plant science (Fromm & Lautner, 2007;Gil et al, 2009;Dziubinska et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation